DynaCT angiography for the diagnosis of bilateral bow hunter's syndrome. Issue 1 (February 2017) - Lu, Tony; Chinnadurai, Ponraj; Anaya-Ayala, Javier E; Diaz, Orlando M
We herein present a rare case of bilateral positional vertebrobasilar insufficiency secondary to mechanical obstruction of the V2 segment of the vertebral artery in a 71-year-old patient presenting with vertigo, occipital headache, tremors and respiratory irregularities. Two-dimensional digital subtraction angiography is the traditional diagnostic imaging standard but does not capture any peri-vascular bony or soft tissue abnormalities that are important to understand the three-dimensional pathophysiology. Intra-procedural cone-beam computed tomography (CT) is an increasingly used diagnostic adjunct, available in most modern angiographic suites that allows for the three-dimensional visualization of the vasculature as well as CT-like soft tissue visualization of its surrounding anatomy. In this case, we report the additional value of three-dimensional reconstructed cone-beam CT angiographic imaging that led to the successful diagnosis of bilateral positional vertebrobasilar disease. The patient subsequently received C4–C6 cervical decompression and fusion and remains symptom free at 1 year follow-up.